Level of Circulating Endothelial Cells and Expression of Nuclear Factor Kappa Beta of Human’s Peripheral Blood Mononuclear Cells in Subjects with Certain Conditions - Titin A Wihastuti; Djanggan Sargowo; Achdiat Agoes; Satuman Satuman; Teuku Heriansyah (Acta Medica Indonesiana, 2014)
Aim: to detect the levels of CEC and expression of NFκB in the three groups of subjects with certain conditions. Methods: this study is an exploratory study using human peripheral blood samples. The study subjects comprised three groups, the group of 23 healthy people, a group of 35 people that has one or more risk factors for vascular disease and a group of 15 vascular disease patients (coronary heart disease, diabetes mellitus, stroke). CEC were isolated from peripheral blood mononuclear cells (PBMC). CEC level is identified through the measurement of CD45 and CD146 by flowcytometry method. NFκB expression is recognized by ELISA method (imgenex, USA). Results: the highest average levels of CEC were found in the sick group (28.6%). The highest average expression of NFκB (924.9495) is found in the group with risk factors. The lowest average expression of NFκB and CEC is found in the healthy group. Statistical analysis of ANOVA at the interval confidence of 95% shows a significant difference (p=0.00) levels of CEC and NFκB expression between the healthy group with the group with the risk of cardiovascular disease (CVD) and patients with known CVD. Conclusion: increase of level CEC and NFκB expression has a strong relationship with vascular disease and its risk factors.